The Productivity of Purse SeineinFishery Port of PekalonganProvince of Central Java - Rajagukguk, Koko Alexando; Yani, Alit Hindri; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in January 2018 at Fishery Port of Pekalongan, Department of Fishery Resource Utilization, Faculty of Fisheries and Marine, University of Riau. The purpose of this study is to calculate the productivity of purse seine and fishing vessels. Productivity in the fishing unit has increased and decreased in each year. The productivity of the highest catching unit in purse seine was 119,617,069 kg/unit/year, while the lowest was 9,809,098 kg /unit/year. For purse seine capture productivity, the highest catching unit productivity is 47,212,20 kg unit/year. The total productivity of the highest purse seine fishermen is 3,604,044 kg/person/year, while the lowest productivity is 2,002,862 kg/person/year. Factors that influence the productivity of mini purse seine catch is the size of the ship (X2). As for several factors that affect the productivity of the catch is not represented the fuel. Keywords: productivity, purse seine,FisheryPort of Pekalongan